Sociodemographic characteristics and disability pensions of frequent attenders in occupational health primary care - a follow-up study in Finland - Tiia Reho; Salla Atkins; Mikko Korhonen; Anna Siukola; Markku Sumanen; Mervi Viljamaa; Jukka Uitti; Riitta Sauni (BMC, 2021)
Abstract Background Work disability is a complex issue that requires preventive efforts from healthcare systems and individuals, and that too often results in disability pensions (DP). While many studies have attempted to characterize risk factors of work disability, many showing for example a link between socioeconomic positions, working conditions and frequent attendance to OH primary care it is not known if frequent attendance is associated with DP despite the sociodemographic factors. This study aims to address this gap and examine the association between frequent attendance to OH primary care and DP, when adjusted by sociodemographic factors. Methods This study combines routine medical record data of an occupational health service provider with comprehensive national registers. Medical record data were used to define groups of frequent attenders to OH primary care (FA) (1-year-FA, 2-year-FA, persistent-FA and non-FA) from 2014 to 2016. The sociodemographic factors (including i.e. educational level, occupational class, unemployment periods) were derived from Statistic Finland and DP decisions were derived from Finnish Centre for Pensions. Association of frequent attendance to OH primary care with DP decisions were analyzed and adjusted by sociodemographic factors. Results In total, 66,381 patients were included. Basic and intermediate education along with manual and lower non-manual work predicted frequent attendance to OH primary care. Unemployment in 2013 did not predict frequent attendance to OH primary care. Frequent attendance to OH primary care was associated with DP within next two years, even when adjusted for sociodemographic factors. The association of frequent attendance to OH primary care with DP grew stronger as high service use persisted over time. Conclusions Frequent attendance to OH primary care is associated with DP risk in the near future despite the underlying sociodemographic differences. Patients using OH primary care services extensively should be identified and rehabilitative needs and measures necessary to continue in the work force should be explored. Sociodemographic issues that co-exist should be explored and considered when planning interventions.